Immunoglobulin allotypes and IgG subclass antibody response to Pseudomonas aeruginosa antigens in chronically infected cystic fibrosis patients. - Pressler, T (1992)
Chronic Pseudomonas aeruginosa lung infection is the leading cause of death in patients with cystic fibrosis (CF). Poor prognosis correlates with a high number of anti-pseudomonas precipitins and with high levels of IgG2 and IgG3 anti-pseudomonas antibodies. Reports of several highly significant associations between certain Gm (genetic markers of IgG on human chromosome 14) and Km (k-type light chain determinants on chromosome 2) phenotypes and immune responsiveness to various antigens suggest that allotype-linked immune response genes do exist in man. Furthermore correlation between Gm types and IgG subclass levels has been reported. A group of 143 CF patients were investigated (31 non-infected and 112 chronic infected). The IgG subclass antibodies to three different P. aeruginosa antigens (P. aeruginosa standard antigen (St-Ag), alginate and LPS) were determined. Immunoglobulin allotypes were determined by haemagglutination inhibition. Samples were typed for G1m(1,2,3, and 17), G2m(23), G3m(5,21), and Km(1,3). Statistical analysis of our data demonstrate that IgG3 anti-pseudomonas antibody levels and Gm markers are related. IgG3 antibody levels to all investigated P. aeruginosa antigens are significantly higher in sera homozygous for Gm(3;5), somewhat lower in heterozygous sera, and significantly lower in sera homozygous for Gm(1,2,17;21). We suggest that genetic differences between the patients may explain the present differences in subclass patterns.